Supporting evidence-based decision-making: Capacity Building through Research. Issue 5 (3rd March 2022) - Conallin, John; Van Cauwenbergh, Nora; Duncan, Nicolette; Zin, Win Win; Lunn, Zau; Htike, Htike; Martin, Greg; Bogaard, Thom; Franca, Mário J.
Abstract: Lack of data inhibits informed decision-making and is a critical challenge in developing countries, many of which are under-resourced in financial, technical and institutional capacity to collect and analyse the required data. This limits the countries' ability to achieve development goals and keeps them dependent on the provision of external resources. Development initiatives often treat capacity building and research as two separate tracks of development. While efforts have been made in the health sector to combine these through project-based learning, this approach is relatively unexplored in the water sector which by its inter-sectoral nature stands to benefit significantly from a more collaborative and solution-oriented development strategy. Capacity Building through Research (CBtR) facilitates data collection and analysis by local researchers, mentored by international experts, strengthening local capacity to produce credible evidence able to inform sustainability-related decision-making. Five case studies piloting CBtR are discussed here and evaluated through criteria of the Dutch Strategy Evaluation Protocol framework. CBtR is shown to be a long-term strategy that requires the strengthening of cross-disciplinary networks to enhance the capacity of water management institutions, which likely contributes to more efficient evidence collection and analysis suitable for decision-makers, leading to greater national resilience and reduced need for external support. HIGHLIGHTS: Project-based Capacity Building through Research (CBtR) initiatives have been piloted in the water sector and assessed. In CBtR, both capacity building and research are integral components of project planning. CBtR enhances the knowledge base and evidence for sustainability-related decision-making. CBtR improves national resilience, while reliance on external development organisations is reduced.